Oxidative burst of Kupffer cells: target for liver injury treatment. - Vrba, Jiri; Modriansky, Martin (Biomedical papers, 2002)
Liver injury, and frequent consequent fibrosis, is the focus of a number of research groups ranging from molecular biologists to clinicians. It encompasses many aspects and approaches. Among biochemical events the role of Kupffer cells, oxidative stress and pro-inflammatory mediators are eminent. In this review we focus on recent findings into use of natural substances for the modulation of oxidative burst as well as production of inflammatory mediators by Kupffer cells.
Keywords: Oxidative stress / Macrophages / Natural substances / Inflammation